Two cases of deflected decentralization Pakistan and Nepal - Lundberg, Paul A. (2002)
This study examines the decentralization strategies of Pakistan and Nepal which undertook decentralization reforms during the same period. Decentralization in these two countries was initiated in response to overcentralization. However, the effects of decentralization have been limited by some peculiarities in the political, economic, social, and security situation of Pakistan and Nepal. This study takes a comparative look at the differences between the two countries and how such have contributed to the slow pace of decentralization. These differences include contrasts in their democratization history, system of government, political stability and insurgency.
Keywords: Central-local relations -- Nepal; Central-local relations -- Pakistan; Decentralization -- Nepal; Decentralization -- Pakistan; Fiscal decentralization -- Nepal; Fiscal decentralization -- Pakistan; Local Government Ordinance 2001 -- Pakistan